ERS International Congress, Madrid, 2019: highlights from the Pulmonary Vascular Diseases Assembly. Issue 4 (13th October 2020) - Ramjug, Sheila; Weatherald, Jason; Sahay, Sandeep; Khoury, Johad; Foris, Vasile; Chandran, Nagaraj; Bokan, Aleksandar; Godinas, Laurent; Delcroix, Marion
The 2019 European Respiratory Society (ERS) International Congress, held in Madrid, Spain, had exciting sessions regarding the field of pulmonary vascular disease. The symposia related to the new ERS/European Society of Cardiology (ESC) Guidelines for the diagnosis and management of acute pulmonary embolism were well received, as were sessions on pulmonary hypertension related to lung disease, demonstrating the concept of pulmonary hypertension not being the rarity that it was previously thought to be. The use of risk stratification in relation to pulmonary arterial hypertension (PAH) was heavily featured and the scientific sessions informing the respiratory community of potential biomarkers and targets for future therapies were thought-provoking. This article discusses highlights of the 2019 pulmonary vascular disease sessions as a summary of current knowledge and practice. We have summarised the key points from the sessions pertaining to the new ERS/ESC Guidelines for the management of acute pulmonary embolism. We have also focused on prognostic factors and potential therapies in pulmonary hypertension related to interstitial lung disease. Relating to PAH, we have reviewed the symposia on risk stratification, along with the use of noninvasive measures and the sessions relating to biomarkers in PAH. This article aims to summarise research presented at #ERSCongress 2019: the new @escardio/@EuroRespSoc guidance on acute PE diagnosis and management, PH in relation to chronic lung disease, and advances in pulmonary arterial hypertension https://bit.ly/3bAUG0o